Tracheostomy Is Safe During Extracorporeal Membrane Oxygenation Support. Issue 6 (June 2020) - Salna, Michael; Tipograf, Yuliya; Liou, Peter; Chicotka, Scott; Biscotti, Mauer; Agerstrand, Cara; Abrams, Darryl; Brodie, Daniel; Bacchetta, Matthew
Abstract : Patients receiving extracorporeal membrane oxygenation (ECMO) often require prolonged mechanical ventilation. Providers may be reluctant to perform tracheostomies on patients during ECMO due to their tenuous clinical status and systemic anticoagulation. We report our experience with performing open and percutaneous tracheostomies on patients supported on ECMO from August 2009 to December 2017. Of the 127 patients who underwent tracheostomy during ECMO support, the median age was 42 years (interquartile range [IQR], 29–54), 99 (78%) patients had venovenous (VV) cannulation, 22 (17%) patients had venoarterial (VA) cannulation, and six (5%) patients had hybrid configurations. Percutaneous tracheostomy was performed in 110 (87%) patients. Median-activated partial thromboplastin time (aPTT) at the time of tracheostomy was 47.5 seconds (IQR, 41–57.6 seconds). The median time from ECMO initiation to tracheostomy was 7 days (IQR, 4–11 days). A total of 55 patients (43%) received packed red blood cell (pRBC) transfusions within 48 hours after tracheostomy with a median transfusion of 2 units (IQR, 1–3). There was no procedural mortality. Overall, 88 (69%) patients survived to decannulation and 74 (58%) survived to hospital discharge. Our experience with the largest published series of tracheostomies during ECMO demonstrates that excellent outcomes can be achieved without significant morbidity.